Design of New Quinazoline Derivative as EGFR (Epidermal Growth Factor Receptor) Inhibitor through Molecular Docking and Dynamics Simulation - Herlina Rasyid; Bambang Purwono; Harno Dwi Pranowo (Indonesian Journal of Chemistry, 2021)
Erlotinib, Afatinib, and WZ4002 are quinazoline derivative compounds and classified as first, second, and third-generation EGFR inhibitor. All inhibitors have been given directly to cancer patients for many years but find some resistance. These three compounds are candidates as the lead compound in designing a new inhibitor. This work aims to design a new potential quinazoline derivative as an EGFR inhibitor focused on the molecular docking result of the lead compound. The research method was started in building a pharmacophore model of the lead compound then used to design a new potential inhibitor by employing the AutoDock 4.2 program. Molecular dynamics simulation evaluates the interaction of all complexes using the Amber15 program. There are three new potential compounds (A1, B1, and C1) whose hydrogen bond interaction in the main catalytic area (Met769 residue). The Molecular Mechanics Generalized Born Surface Area (MM-GBSA) binding energy calculation shows that B1 and C1 compounds have lower binding energies than erlotinib as a positive control, which indicates that B1 and C1 are potential as EGFR inhibitor.